Gambaran Gejala Computer Vision Syndrome Pada Mahasiswa Fakultas Kedokteran Universitas HKBP Nommensen MedanTahun 2019/2020 - Halawa, Evan Marteen (Faculty of Medicine, Universitas Andalas, 2024)
Background: The use of computers among students is now a necessary, especially for medical students both study and entertainment. This situation can increase the risk of Computer Vision Syndrome (CVS). Computer Vision Syndrome (CVS) is a bunch of symptoms on eye and vision-related problems by prolonged use of computers (such as tablets, e-readers, smartphones, etc.). This study aimed to find out the representation of CVS symptoms experienced by medical students in Medical Faculty of Universitas HKBP Nommensen Medan;